Where the Action Is Sites of Contemporary Sōtō Buddhism - Rowe, Mark Michael (2004)
This article considers reactions at various levels of the Sōtō sect to the problems of funerary Buddhism. There is a widening gap, not only between the necessities of mortuary practice at local temples (both rural and urban) and the doctrine of no-self ostensibly embodied in the foundational texts of Dogen and Keizan, but also within the very organizational structures of the Sōtō sect itself. From its official publications and regional conferences to innovative strategies being developed at individual temples, I argue that, far from being a unified body, Sōtō Buddhism speaks with an array of competing and often contradictory voices. The diversity of Sōtō responses to the "mortuary problem" reveals intriguing disconnects between the research arm of the sect, those responsible for training priests, and the daily realities of local temples.
Keywords: Ceremonies; Funerals; Priests; Religious rituals; Religious Studies; Research facilities; Sectarianism; Temples; Zen Buddhism